The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1590/s1806-66902011000200035
|View full text |Cite
|
Sign up to set email alerts
|

Componentes estruturais do resíduo pós-corte em capim-massai adubado com cinco doses de nitrogênio

Abstract: Resumo -Objetivou-se avaliar os componentes da biomassa do resíduo pós-corte em capim-massai submetido a cinco doses de nitrogênio (0; 150; 300; 450 e 600 mg N dm -3 de solo) num delineamento inteiramente casualizado, com cinco repetições (vasos) em casa de vegetação. Avaliaram-se a altura residual, a densidade populacional de perfilhos (DPP), a massa seca de forragem total residual (MSFTr), de forragem verde residual (MSFVr), de forragem morta residual (MSFMr), de lâmina foliar verde residual (MSLVr), de colm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…The LBMr was lower than that observed by Emerenciano Neto et al (2013) due to the higher post-grazing height used by the authors, who found 764.1 kg ha -1 DM at 25 cm high. According to Lopes et al (2011), the remaining amount of leaves indicated the level of the animals grazing pressure. Thus, the small amount of remaining leaves indicated that the grazing pressure was high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LBMr was lower than that observed by Emerenciano Neto et al (2013) due to the higher post-grazing height used by the authors, who found 764.1 kg ha -1 DM at 25 cm high. According to Lopes et al (2011), the remaining amount of leaves indicated the level of the animals grazing pressure. Thus, the small amount of remaining leaves indicated that the grazing pressure was high.…”
Section: Resultsmentioning
confidence: 99%
“…Lower participation of the leaf blades in the post-grazing dramatically reduced the photosynthetic rate of plants during regrowth caused by the sharp drop in the reducing sugars represented by the monosaccharides glucose and fructose, which are the first stable organic compounds synthesized by plants during photosynthesis (Alexandrino et al, 2008). According to Lopes et al (2011), the largest leaf blade mass in post-grazing resulted in better regrowth condition for the plants. This decreased the participation of the stem reserves to form new leaves and quickly restored the total non-structural carbohydrates, hence reducing the pasture regrowth period.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is possible that the cut of the plants at 15 cm (residue) eliminated the apical meristem of the plants kept at 80 cm, resulting in the death of the tiller, which was evidenced by Lopes et al (2011). The regeneration capacity of leaf tissue is one of the main reasons tropical forages persist after cutting, due to the emission of leaves from the apical meristem, which remain below the cutting and/or grazing height.…”
Section: Resultsmentioning
confidence: 99%
“…The greater participation of leaf blades in the forage mass verified in the spring of 2014 and summer of 2015 (Table 2) for both sources of urea was due to the higher frequency of cuts (up to three cuts in the same season) when compared to the others, due to the high temperatures and the increase in the precipitation that favored the growth of the plants, together with the better utilization of the nitrogen fertilizer, accelerating tissue renewal, tillering and production of leaf blades, as highlighted by Lopes et al (2011). The average proportion of leaf blades in relation to the total forage produced in the present experiment (82.0%) was similar to that obtained by Emerenciano Neto et al (2016) and higher than the 63% observed by Emerenciano Neto et al (2013), both for Massai grass.…”
Section: Resultsmentioning
confidence: 97%